Prediction of Oil Density using Group Method of Data Handling (GMDH) Approach and the Effect of Reducing Correlating Parameters; A Comparative Study - Moktar, Nur Syazwani (Universiti Teknologi Petronas, 2013)
Reservoir fluid or PVT properties are one of the most important elements in petroleum engineering, especially in reservoir studies. It is required in material balance, reservoir simulation, volumetric calculations and others. With the laboratory studies and the aids of PVT correlations, PVT properties can be effectively obtained. PVT correlations existed in the oil and gas industry is widely used when the experimental data cannot be obtained or no fluid samples are available. However, some of the empirical correlations in the literature are controversial in aspects of its accuracy, validity and range of applicability. Recently, group method of data handling (GMDH) is introduced in the petroleum industry as another alternative to improve the accuracy of existing PVT correlations. This research proposes GMDH approach as a modeling tool for predicting crude oil density at bubble-point pressure. The objective of this research is to study the capability of GMDH in modeling oil density. The new oil density model incorporates three (3) correlating parameters: (1) bubble-point oil formation volume factor, (2) solution gas-oil ratio and (3) API gravity. A comparative study is carried out to compare the performance of the new oil density model with other existing correlations. The results obtained show that the oil density model with GMDH is more accurate and outperforms other known correlations.